Electroactive polymeric nanocomposite BC-g-(Fe3O4/GO) materials for bone tissue engineering: in vitro evaluations. Issue 11 (24th July 2022) - Khan, Muhammad Umar Aslam; Rizwan, Muhammad; Razak, Saiful Izwan Abd; Hassan, Anwarul; Rasheed, Tahir; Bilal, Muhammad
Abstract: Tissue engineering is a cutting-edge approach for using advanced biomaterials to treat defective bone to get desired clinical results. In bone tissue engineering, the scaffolds must have the desired physicochemical and biomechanical natural properties in order to regenerate complicated defective bone. For the first time, polymeric nanocomposite material was developed using cellulose and co-dispersed nanosystem (Fe3 O4 /GO) by free radical polymerization to fabricate porous polymeric scaffolds via freeze drying. Various characterizations techniques, such as Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM)/energy dispersive X-ray (EDX), and universal testing machine (UTM) were used to investigate structural, morphological, and mechanical properties. Swelling, biodegradation, and wetting analysis were also performed to evaluate their physicochemical behavior. Intercalation of Fe3 O4 nanoparticles into GO-sheets promoted their dispersion into the polymeric matrix. All porous scaffolds possessed a well-interconnected porous structure, while the synergistic effect of Fe3 O4 /GO reinforces the mechanical strength of porous scaffolds. The compressive strength and Young's modulus were increased by increasing Fe3 O4 amount, and maximum mechanical strength was found in HFG-4 and least in HFG-1. However, these porous scaffolds have different swelling and biodegradation behavior due to the variable Fe3 O4 intercalations into GO-sheets. Antibacterial activities of porous scaffolds were studied against severe Gram-positive and Gram-negative pathogens and increased Fe3 O4 amount in nanosystem increased the antibacterial activities. The cell viability and morphology of pre-osteoblast ( MC3T3-E1 ) cell lines were studied against porous scaffolds and increased cell viability and proliferation were observed from HFG-1 to HFG-4. Hence, the electroactive material could be the potential material for bone tissue engineering.